Projects to promote school success: challenges and opportunities - Pereira, Gorete (2023)
This communication is the result of an investigation that sought to study projects to promote school success, implemented in some schools in the Autonomous Region of Madeira (RAM). Considering the principles, guidelines and standards present in Regional Legislative Decree No. 11/2020/M, of July 29th and Ordinance No. 357/2021, of June 29th, schools were encouraged to design and develop projects promoting academic success. We intend to analyze educational policy discourses regarding curricular, pedagogical and organizational innovation plans; understand the narrative of schools exercising their autonomy, through the analysis of the aforementioned plans; identify the processes for implementing the options and measures taken by schools with a view to promoting better learning. Characterized by its qualitative nature, the research consisted of a multiple case study (Yin, 2003). Interviews were carried out with those responsible for the projects, followed by document analysis (Lüdke e André, 1986), content analysis (Bardin, 1995) and data triangulation. The evidence points to the promotion of learning and the development of skills and attitudes included in the areas of competences of the Profile of Students Leaving Compulsory Schooling.